Wild Plant Assessment for Heavy Metal Phytoremediation Potential along the Mafic and Ultramafic Terrain in Northern Pakistan - Muhammad, Said (Hindawi Publishing Corporation, 2013)
This study investigates the wild plant species for their phytoremediation potential of macro and trace metals (MTM). For this purpose, soil and wild plant species samples were collected along mafic and ultramafic terrain in the Jijal, Dubair, and Alpuri areas of Kohistan region, northern Pakistan. These samples were analyzed for the concentrations of MTM (Na, K, Ca, Mg, Fe, Mn, Pb, Zn, Cd, Cu, Cr, Ni, and Co) using atomic absorption spectrometer (AAS-PEA-700). Soil showed significant (P < .001) contamination level, while plants had greater variability in metal uptake from the contaminated sites. Plant species such as Selaginella jacquemontii, Rumex hastatus, and Plectranthus rugosus showed multifold enrichment factor (EF) of Fe, Mn, Cr, Ni, and Co as compared to background area. Results revealed that these wild plant species have the ability to uptake and accumulate higher metals concentration. Therefore, these plant species may be used for phytoremediation of metals contaminated soil. However, higher MTM concentrations in the wild plant species could cause environmental hazards in the study area, as selected metals (Fe, Mn, Cr, Ni, Co, and Pb) have toxicological concerns.